Preparation and Application of Modified Vermiculite Adsorption Materials - Huicong DU; Kaifang WEI; Yang LU; Yunhe LIU; Wei WANG; Haizhang MENG; Ping LAN; Lihong LAN (Kuangchan zonghe liyong, 2025)
β-Cd polymer (KACD) was prepared by modifying β-Cd with KH560 at alkaline conditions, and then the polymer was loaded onto vermiculite to prepare β-Cd modified vermiculite composite (KACDS). Based on the adsorption capacity of methylene blue by KACDS, the optimum preparation process of β-cyclodextrin modified vermiculite was determined by single factor method: the mass ratio of acidified vermiculite to KACD was 1∶4, the modification temperature was 65 ℃, and the modification time was 12 h. Test results of adsorption of methylene blue (MB) and Gentian violet (GV) by KACDS showed that the adsorption performance of the composite is most significantly affected by the pH value of the system. When the pH value is 9, the adsorption rate of KACDS on MB is the highest 99%, and when the pH value is 7, the adsorption rate of the composite on the GV solution with the initial concentration of 8 mg/L for 48 min is the highest 93.19%. The adsorption properties of MB and GV are better than those of vermiculite. By analyzing the model fitted by the adsorption kinetics experiment, it can be seen that the adsorption process of GV by the cross-linked material is consistent with the second-order kinetic model, which belongs to the chemical adsorption process and is less affected by temperature.